THE ROLE OF LEADERSHIP AND COLLABORATION IN DRIVING SUSTAINABLE PORT MANAGEMENT - Simanjuntak, Pargaulan Dwikora; Guntoro, R. Herlan (Erudio Journal of Educational Innovation, 2025)
Ports play a crucial role in global trade and economic development, yet they are also significant contributors to environmental degradation. The increasing pressure to adopt sustainable port management strategies requires an understanding of how leadership and collaboration influence the implementation of sustainability initiatives. Previous research has primarily focused on regulatory compliance and technological advancements but has not sufficiently explored the role of maritime professionals in shaping sustainability outcomes. This study examines how leadership styles and stakeholder collaboration impact sustainable port operations, identifying key challenges and best practices. Using a qualitative research approach, data was collected through semi-structured interviews and focus groups with harbormasters, port authority officers, maritime entrepreneurs, lecturers, and graduates. The findings indicate that leadership is the most influential factor in driving sustainability, scoring 9.3/10, while stakeholder collaboration plays a crucial role in policy implementation (9.0/10). However, economic constraints, regulatory inconsistencies, and gaps in sustainability training (8.7/10) continue to hinder progress. The study concludes that strong leadership, improved inter-sector collaboration, and enhanced sustainability education are essential for overcoming these challenges. These findings provide practical recommendations for policymakers, port authorities, and maritime educators to strengthen sustainability efforts within global port management.